Physiotherapy in Respiratory Care / An Evidence - Based Approach to Respiratory and Cardiac Management: Third Edition - Hough Alexandra; Nelson Thornes (2001)
This book continues to use a practical, problem-solving approach, based on research, to provide clarity of thought and to challenge traditional assumptions. Preface, Acknowledgements, Physiological Basis of Clinical Practice, Clinical Assessment, Obstructive Disorders, Restrictive and other Disorders, General Management, Physiotherapy to Increase Lung Volume, Physiotherapy to Reduce the Work of Breathing, Physiotherapy to Clear Secretions, Pulmonary Rehabilitation, Physiotherapy for People Undergoing Surgery, Physiotherapy for Specific Groups of People, Intensive Care and Monitoring and Support, Mechanical Ventilation, Physiotherapy for Patients in Intensive Care, Disorders in Intensive Care Patients, Physiotherapy for Children and Infants, Evaluation of Respiratory Physiotherapy, Glossary of Abbreviations and Definitions and Symbols and Values, Appendices, References, Index.